Adaptasi Komunikasi dan Penggunaan Bahasa Jepang di Tempat Kerja: Studi Pengalaman Mahasiswa Magang Indonesia di Jepang - Sri Muryati; Bekti Setio Astuti; Trismanto Trismanto; Vamelia Aurina Pramandhani; Septa Wiki Dwi Cahyani (Vocational College of Diponegoro University, 2026)
This study aims to analyze the linguistic and sociolinguistic competence as well as language adaptation strategies of Indonesian vocational students participating in internship programs in Japan. The study is theoretically grounded in Intercultural Communicative Competence (Byram, 1997) and Communication Accommodation Theory (Giles, 1991). A qualitative-embedded survey approach was employed, utilizing questionnaire data and thematic analysis from 52 respondents out of a total population of 70 internship students. The findings indicate that while students are generally able to perform basic workplace communication, they experience notable difficulties in using formal Japanese, particularly keigo and industry-specific expressions. Online learning experiences also influence the development of language competence and cultural awareness. The study concludes that Japanese language competence and adaptive communication strategies play an important role in enhancing workplace performance and facilitating intercultural integration.